Late Stone Age Hunters of the British Isles. - Smith, Christopher (Routledge, 1992)
Places the evidence for the Late Upper Palaeolithic and Mesolithic periods, conventionally viewed mainly in terms of stone tool typologies, in a wider ecological and geographical context.